Knowledge, Behaviour and Utilization of Integrated Health Services Post in Working Area Ratu Agung Community Health Center Bengkulu - Santoso Ujang Effendi; Buyung Keraman; Edo Darmasyah Putra (Jurnal Sains Kesehatan, 2018)
Good utilization of Integrated Health Services Post was very influential on monitoring the growth and development of  under five children under five. This study aimed to determine the relationship between knowledge and attitude of mother with the utilization of  Integrated Health Services Post by mothers of under five children in working area Ratu Agung  Community Health Center Bengkulu. The type of this research was Analytical Survey and used Cross Sectional design. The population of  this study  were all mothers who had 7-23 months children amounted 512 mothers. Sampling technique was Proportional Random Sampling. The total samples were  84 samples. Data used in this study are primary data through the distribution of questionnaires given to mothers. Data analiysed by using Chi-Square (χ2) and Contingency Coefficient (C) statistics test. The result of the research were  44 mothers (52,4%) had enough knowledge, 56 mothers (66,7%) had favorable behavior, 53 mothers (63,1%) utilized Integrated Health Services Post, and there was significant relationship  between knowledge and attitude of mothers with the usage of Integrated Health Services Post in the working area of Ratu Agung Community Health Center Bengkulu with medium category. Ratu Agung Community Health Center can increase the knowledge of the community by doing education about the importance of Integrated Health Services Post so that community, especially mothers with under five  children can understand the importance of Integrated Health Services Post and can visit regularly every month.                                                                               Keywords :  attitude, knowledge,  utilization  of   integrated  health  services  post